Simuliidae (Diptera, Nematocera) do Estado de São Paulo - Pepinelli, Mateus (2008)
The lack of knowledge about ecology and taxonomy of black flies (Diptera: Simuliidae) in several regions of Brazil restrict the advance of programs about population control, environmental impact assessment and conservation of biodiversity. With the aim of assessing the diversity of black fly species in the State of São Paulo, we realized collections in 151 localities, including from low order streams to the main rivers of all hydrographic basins in this State. We collected and identified 43 species, of which Simulium incrustatum, S. pertinax, S. subpallidum, S. nigrimanum and S. inaequale were the most frequent species in streams under anthropogenic influence and, consequently, had the widest geographic distribution in the State of São Paulo. Two other species were also frequent, S. subnigrum and S. subclavibranchium had its geographic distribution restrict to Atlantic Forest areas. Both species belong to the Inaequalium subgenus. The species within the Inaequalium subgenus usually live in forested streams. Four species from this subgenus showed morphological variations that became difficult its identification. The study of CO1 gene (DNA Barcode), morphological variations and geographic distribution allowed separated, partially, the boundaries among the following species: S. nahimi and S. subclavibranchium with well defined limits. S. subnigrum and S. nogueirai were not possible to distinguish and the results showed that may be a species complex.